Antifungal Activity of Chinese Belt Herb (Peperomia Pellucida L. Kunth) Ethanol Extract on the Growth of Candida Albicans - Widayanti, Ni Putu; Laksmita W., Ayu Saka; Apriyanthi, Desak Putu Risky Vidika; Widnyani, Ni Made (Indonesian Journal of Global Health Research, 2024)
When the host's phagocytic resistance diminishes, Candida albicans can enter the bloodstream and cause a systemic fungal infection known as candidiasis. One fungus that has become resistant to antifungals is Candida albicans. The herb sirih cina is one way to discover novel antifungals made of natural elements. This study aims to determine the antifungal activity of Chinese betel leaf extract against the growth of the Candida albicans fungus. The sirih cina plant (Peperomia pellucida L. Kunth) was used in this experimental work, which used 70% ethanol as a solvent for the extraction process using maceration. Alkaloids, flavonoids, tannins, saponins, and phenolics are among the secondary metabolites found in the ethanol extract of the Sirih cina plant. Using the well diffusion test method, the antifungal efficiency of the ethanol extract of the Sirih cina plant at concentrations of 25%, 50%, 75%, and 100% was evaluated. Candida albicans growth is inhibited by the ethanol extract of the Sirih Cincina plant, which is categorized as medium category and has the highest inhibition zone diameter at 100% concentration of 8.20 ± 0.14 mm.